2020
DOI: 10.1101/2020.05.30.125013
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Structure and lipid dynamics in theA. baumanniimaintenance of lipid asymmetry (MLA) inner membrane complex

Abstract: 24The maintenance of lipid asymmetry (MLA) system is involved in lipid transport from/to 25 the outer membrane in gram-negative bacteria, and contributes to broad-range 26 antibiotic resistance. Here, we report the cryo-EM structure of the A. baumannii 27 MlaBDEF core complex, in the apo, ADP-and AppNHp-bound states. This reveals 28 multiple lipid binding sites, and suggests a mechanism for their transport. 29 30 31Gram-negative bacteria are enveloped by two lipid bilayers, separated by the periplasmic 32 spac… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 53 publications
1
11
0
Order By: Relevance
“…On the other hand, prior studies indicated that the Mla system is an importer (Malinverni and Silhavy, 2009;Chong, Woo and Chng, 2015;Powers and Trent, 2018;Yeow et al, 2018), and in vitro reconstitution and transport assays suggest that MlaFEDB may be bi-directional, with a preference for import (retrograde transport) (Tang et al, 2020). Concurrently with our preprint, two other groups also reported structures of the MlaFEDB complex on BioRxiv (Coudray et al, 2020;Mann et al, 2020;Tang et al, 2020), and these structures appear to be similar overall, although the PDB coordinates…”
Section: Discussionsupporting
confidence: 71%
“…On the other hand, prior studies indicated that the Mla system is an importer (Malinverni and Silhavy, 2009;Chong, Woo and Chng, 2015;Powers and Trent, 2018;Yeow et al, 2018), and in vitro reconstitution and transport assays suggest that MlaFEDB may be bi-directional, with a preference for import (retrograde transport) (Tang et al, 2020). Concurrently with our preprint, two other groups also reported structures of the MlaFEDB complex on BioRxiv (Coudray et al, 2020;Mann et al, 2020;Tang et al, 2020), and these structures appear to be similar overall, although the PDB coordinates…”
Section: Discussionsupporting
confidence: 71%
“…It is noteworthy that the proposed manner of lipid binding to MlaFEDB differs significantly among all three pre-prints posted around the same time. Our structure and the other E. coli MlaFEDB structure described by Tang, et al describe lipid binding to the outward-open pocket of MlaE (Tang et al, 2020), while the Acinetobacter baumannii MlaFEDB described by Mann, et al describes lipid binding sites at the pore of MlaD as well as six additional lipidbinding sites in between the pore loops of each of the six MCE domains in the MlaD ring (Mann et al, 2020). Tang et al observed density assigned to a single phospholipid bound in the outward-open pocket of MlaFEDB, with the head group facing towards the core of the MlaE dimer and tails pointing towards the MlaD pore.…”
Section: Discussionmentioning
confidence: 88%
“…Of note, at the time of writing, publicly available, yet unpublished structures of the lipid transporter complex MlaFEDB of Gram ‐negative bacteria reveal some resemblance of MlaE to LptF/G and MacB. However, the number of TM helices differs between LptFG (six TM helices), MlaE (five TM helices), and MacB (four TM helices) [45–48] (Table S6 and Fig. S1).…”
Section: Figmentioning
confidence: 99%